Grundtvig, angelsakserne og Sidste Digt - Lundgreen-Nielsen, Flemming (Grundtvig-Studier, 1999)
On Grundtvig and Anglo-Saxon Poetry, esp. Regarding his Last Poem By Flemming Lundgreen-Nielsen The article discusses the degree of Anglo-Saxon influence on Grundtvig’s poetical imagery and on his conception of the transition from earthly life through death to eternal life and salvation. S.A.J. Bradley’s emphasis on Anglo-Saxon reminiscences in Grundtvig’s farewell poem, 1872 (in Heritage and Prophecy, 1993) is acknowledged as as a valuable contribution to the understanding of the text; yet his moderation of the influence from the poetical practice of Danish 18th century lyrical poets and from the Greek myth of Charon, the ferryman of death, is questioned in the light of Danish 19lh century reception of these recent writers and of Grundtvig’s own preoccupation with Greek myths and history in the 1840s. William Michelsen’s interpretation of Grundtvig’s last poem (in Grundtvig Studier 1995) is discussed in some detail, relating to the idea of the action as a reversal, i.e. Christianization, of the Charon or Valhal myth. Finally Merete Bøye’s attempt (in Grundtvig Studier 1998) to establish a dichotomy borrowed from Anglo-Saxon Christian poetry of Hall and Ocean (»Hal« and »Hav«) in Grundtvig’s writings, understood as symbolic locations in an eschatological perspective, is supplemented by information of the use of these words and terms in the literary universe of Grundtvig and his contemporaries. The article concludes with an 1832 quotation from Grundtvig to the effect that in true poetry and true prophecies, produced by skalds who are not professional soothsayers, ambiguity is the point, allowing each reader to make what he can of it. Therefore a comprehension of Grundtvig’s last poem should not be narrowed down to the con-sideration of only one pattern, in this case from Anglo-Saxon poetry.